The pandemic as a legal prerequisite for the introduction of some special legal regimes - N. O. Rastorhuieva (Law and Safety)
The article is devoted to the study of the pandemic as a legal prerequisite for the introduction of special legal regimes. Approaches to the definition of the term “pandemic” that occur in various fields are analyzed. It is noted that the pandemic is closely related to the epidemic in the scientific literature. That is, today there is a statement that the spread of an epidemic to several countries or continents is called a pandemic. It is claimed that the understanding of the essence of the pandemic as a phenomenon from the field of medicine and social relations shows that the pandemic causes not only medical and other social consequences, but also legal ones.